2012
DOI: 10.2343/geochemj.1.0166
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and isotopic characterization of the thermomineral water of Terme Sibarite springs (Northern Calabria, Italy)

Abstract: both dissolved sulfate and sulfide have been included among the used geochemical tools to investigate the provenance of dissolved sulfur species and the active processes controlling their concentrations and isotopic ratios. The thermomineral waters discharged by the Terme Sibarite have been known and used therapeutically since Roman times, owing to the large flow rate, in the order of 130 L s-1 as whole (Arena, 1978). Up to now, they were the subject of regional geochemical studies, chiefly aimed at the survei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…This is consistent with summer southwest monsoon precipitation in the region coming directly from the Bay of Bengal. The d-excess value in the precipitation directly from the Bay of Bengal is lower due to the high relative humidity of the sea surface [37][38][39][40][41][42]. For this reason, the precipitation is coincident with the annual peak of snowmelt during the wet season.…”
Section: Study Areasmentioning
confidence: 99%
“…This is consistent with summer southwest monsoon precipitation in the region coming directly from the Bay of Bengal. The d-excess value in the precipitation directly from the Bay of Bengal is lower due to the high relative humidity of the sea surface [37][38][39][40][41][42]. For this reason, the precipitation is coincident with the annual peak of snowmelt during the wet season.…”
Section: Study Areasmentioning
confidence: 99%
“…Tectonic activity in the major fault was responsible for exhumation of carbonate rocks and gave rise to aquifer circulation. Thermal springs represent the subsurface upwelling of the Sibari thermal system and sulfate waters (Apollaro et al, 2012). The chemical characteristics of the waters suggest that the oxidation of H 2 S to sulfuric acid favored by the mixing between thermal water (Ca-SO 4 to Ca-SO 4 -HCO 3 in composition) and fresh water (Ca-HCO 3 to Ca-Mg-HCO 3 (Apollaro et al, 2012) infiltrating along the major fault was the main source of aggressiveness and dissolution of limestone.…”
Section: Geological Settingmentioning
confidence: 99%
“…Thermal springs represent the subsurface upwelling of the Sibari thermal system and sulfate waters (Apollaro et al, 2012). The chemical characteristics of the waters suggest that the oxidation of H 2 S to sulfuric acid favored by the mixing between thermal water (Ca-SO 4 to Ca-SO 4 -HCO 3 in composition) and fresh water (Ca-HCO 3 to Ca-Mg-HCO 3 (Apollaro et al, 2012) infiltrating along the major fault was the main source of aggressiveness and dissolution of limestone. The progressive fall in the piezometric level is due to gradual exhumation of the top and lateral aquicludes, represented by shale and phyllite displaced by major faults (Galdenzi, 1997) (Fig.…”
Section: Geological Settingmentioning
confidence: 99%
“…Stable isotope such as oxygen (δ 18 O), deuterium (δD), chlorine ( 37 Cl), carbon ( 13 C) and sulfur ( 34 S) and radioactive isotope tritium ( 3 H) and carbon ( 14 C) are the most commonly used environmental isotopes in water science. Altitude, latitude, amount of rainfall and continental effects were inferred to be the influencing factors for the variation of isotopes composition [42,43].The Krishnagiri district contains various lithologies with a complex geology, where the groundwater chemistry is mainly controlled by the geogenic processes. Previous studies in this region has shown that the fluoride in the groundwater was released from the magnesium bearing minerals during weathering [44].…”
mentioning
confidence: 99%
“…Stable isotope such as oxygen (δ 18 O), deuterium (δD), chlorine ( 37 Cl), carbon ( 13 C) and sulfur ( 34 S) and radioactive isotope tritium ( 3 H) and carbon ( 14 C) are the most commonly used environmental isotopes in water science. Altitude, latitude, amount of rainfall and continental effects were inferred to be the influencing factors for the variation of isotopes composition [42,43].…”
mentioning
confidence: 99%